'Hong Kong can afford a typhoon or two': British discussions of revolving storms. Issue 3 (September 2021) - Huang, Chi Chi
Abstract: This article examines the way in which the British press reported on typhoons that affected Hong Kong during the nineteenth and early twentieth centuries. Typhoons were a significant element in the narration of the British Empire, featuring frequently in British accounts of their involvements in the Far East, where Hong Kong was its only colony. I suggest that these accounts need to be considered alongside the consolidation of the 'tropics' as a region in British perceptions, and in doing so, this article opens discussions of the study of tropicality to the consideration not just of climate, but also of the significance of singular weather events. This article argues that the cultural representations of typhoons in the British press were a tool of 'othering'. In particular, there were two significant shifts around the 1880s in these reports. First, the term 'typhoon' became tied to these types of storms that affected Hong Kong. Second, the stories that were told about typhoon events emphasized British heroism and colonial management. Both these shifts in reporting stripped away the weather wisdom that British sailors had earlier identified in the local population.